1998
DOI: 10.1126/science.279.5358.1903
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Aggregates of Rod-Coil Block Copolymers and Their Solubilization and Encapsulation of Fullerenes

Abstract: Amphiphilic poly(phenylquinoline)-block-polystyrene rod-coil diblock copolymers were observed to self-organize into robust, micrometer-scale, spherical, vesicular, cylindrical, and lamellar aggregates from solution. These diverse aggregate morphologies were seen at each composition, but their size scale decreased with a decreasing fraction of the rigid-rod block. Compared to coil-coil block copolymer micelles, the present aggregates are larger by about two orders of magnitude and have aggregation numbers of ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
557
1
10

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 868 publications
(580 citation statements)
references
References 43 publications
5
557
1
10
Order By: Relevance
“…In the past, a great deal of theoretical 1-10 and experimental efforts [11][12][13][14][15][16] have been made in understanding their characteristics in solutions with concentrations ranging from dilute to concentrated. One of the remarkable discoveries in the last century is the theory of simple electrolytes made by Debye and Hückel, 17 where electrostatic interactions get screened ͑colloquially referred to as the Debye screening͒.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, a great deal of theoretical 1-10 and experimental efforts [11][12][13][14][15][16] have been made in understanding their characteristics in solutions with concentrations ranging from dilute to concentrated. One of the remarkable discoveries in the last century is the theory of simple electrolytes made by Debye and Hückel, 17 where electrostatic interactions get screened ͑colloquially referred to as the Debye screening͒.…”
Section: Introductionmentioning
confidence: 99%
“…They typically reveal unique self-assembly nanostructures and semiconducting characteristics [32][33][34][35][36]. Various kinds of copolymers were designed, synthesized and incorporated into BHJ with remarkable PCE improvements and/or PCE preservation.…”
Section: Copolymermentioning
confidence: 99%
“…Jenekhe et al found that rod−coil copolymers could selfassemble to form hollow nanospheres directly in their selective solvent (a solvent only dissolve one block of the copolymers). 21 Over the past 10 years, this convenient method has aroused many researcher's interest. 22−24 Recently, we developed a novel approach to prepare rod−coil complexes using the selective inclusion complexation between CD and copolymers.…”
mentioning
confidence: 99%